Pastoral Agriculture in the Post-industrial Age: Building Functional Integrity and Realising Potential - Perley, Christopher J. K. (Frontiers in Sustainable Food Systems, 2021)
The potential of pastoral land use to create positive environmental, economic, and social outcomes is constrained by a “way of seeing” land and people through the eyes of Modernity and mechanical determinism. That ontology of land is compounded and reinforced by positivism, and the associated hierarchical and dis-integrated epistemology around the culture:nature nexus – including what is seen as “objective” science and technology driving practise. Both the ontology and epistemology of our Modern land use culture drive a reduction of ethics, relationship, and meaning to the measured utility of either production or dollars within a “resource sufficiency” view of the land factory. The consequence is not just the non-realisation of potential synergies and multiple functions underpinning value and resilience within the socio-ecological systems associated with pastoral land. It also degrades the “functional integrity” of those integrated systems and increases the fragility and multiple negative outcomes to local economic, environmental, and social functions. This study examines the underlying philosophical thoughtscapes of Modern agri-business models and contrasts those models with the emerging alternatives: from reducible universally-quantifiable machines to post-industrial thought; including post-normal science, integrated complex adaptive systems, and emerging work shifting homogeneous “economies of scale” industrialism to realising potential “economies of scope” by building functional and self-organising systems. It further examines the potential scope to be gained using three specific examples: multi-functional integrated landscapes, resilience theory specific to drought, and market value chains.